Philosophical Approaches in Educational Research - Zrudlo (Philosophical Inquiry in Education, 2024)
This paper suggests ways in which the profile of philosophical research in education could be raised, to demonstrate that it is legitimate and genuinely productive to engage in non-empirical research in education. I begin with some historical context for philosophical research in education, exploring the approach known as “conceptual analysis” as it was practiced some decades ago. I then identify four different ways of engaging in philosophical research in education today, namely, (1) a contemporary version of conceptual analysis, (2) a hermeneutic approach, (3) the philosophy of educational content, and (4) the philosophy of quantitative methodologies. I conclude by identifying three practical strategies for graduate students and researchers in the field, which touch on doctoral training, teacher education, and interdisciplinary or generalist research efforts in education.